MAJAPAHIT PUN RUNTUH KARENA ULAH PARA ELIT POLITIKNYA - Baskoro Daru Tjahjono (Berkala Arkeologi, 2004)
From the beginning of its establishment, Majapahit could not escape the actions of the political elites who tried to break the unity of the Majapahit kingdom. This is due to their dissatisfaction with the king's leadership or dissatisfaction with the position they received. When Raden Wijaya had become king he was abandoned by some of his colleagues at the time of facing Jayakatwang and Kubhilai Khan's army. Although they had obtained high positions but some of them were not satisfied with the awards or positions given by the king. Ranggalawe who was not appointed as a patih (duke), was against the king so there was a war called Paranggalawe in 1217 C (1295 AD).